Boerhaave's Syndrome: Still a Diagnostic and Therapeutic Challenge in the 21st Century - J. Spapen; J. De Regt; K. Nieboer; G. Verfaillie; P. M. Honoré; H. Spapen (Case Reports in Critical Care)
Boerhaave's syndrome is a rare but potentially fatal condition characterised by a transmural tear of the distal oesophagus induced by a sudden increase in pressure. Diagnosis is challenging as the classic triad of vomiting, abdominal or chest pain, and subcutaneous emphysema is absent in many patients. Management is multidisciplinary and relies on rapid, distinct, and repeated imaging. Treatment has not been standardised and may be conservative, endoscopic, or surgical. We present a typical case which illustrates possible diagnostic pitfalls and the therapeutic conundrum surrounding management of the syndrome. Based on time of presentation and eventual presence of sepsis, a therapeutic algorithm is proposed.